Aplikasi Sistem Pakar Dengan Metode Forward Chaining Dan Certainty Factor Untuk Mendeteksi Penyakit Ayam - Terisia, Vany; Yusuf, Diana (Jurnal Sistem Informasi (JUSIN), 2020)
The development of computer technology now is really fast. The computer is not only used as a tool to complete the work of humans but can also run applications designed to access information quickly. Application of expert system application is moved to a computer expert knowledge. So the computer could also resolve the problem as usual is done by specialists. Expert system has been widely developed in various fields, including the field of animal husbandry. Chicken breeders usually get the chicken disease information from the livestock extension officers. But sometimes often constrained because the number of extension officers of the cattle that are not evenly distributed in each area. Therefore, the breeder can access information about diseases of chicken with the help of the method of Forward Chaining and Certainty Factor into the making of the application. The resulting application is an expert system for detecting diseases of chickens that could be used to assist farmers in obtaining information about the disease of chickens and handling solutions.